2014
DOI: 10.1111/trf.12614
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib for chronic relapsing thrombotic thrombocytopenic purpura: a case report

Abstract: Bortezomib may serve as an adjunct treatment in patients with acquired TTP who exhibit an incomplete response or are refractory to conventional management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…[65][66][67][68] Shortt et al reported on a case of a woman with TTP who was refractory to PEX, prednisone, cyclophosphamide, rituximab, and NAC, despite having documented depletion of B cells within her bone marrow.…”
Section: Bortezomibmentioning
confidence: 99%
“…[65][66][67][68] Shortt et al reported on a case of a woman with TTP who was refractory to PEX, prednisone, cyclophosphamide, rituximab, and NAC, despite having documented depletion of B cells within her bone marrow.…”
Section: Bortezomibmentioning
confidence: 99%
“…Its mechanism of action in TTP is thought to be due to the elimination of plasma cells that produce the autoantibodies against ADAMTS13. The evidence for the use of this drug is still limited to case reports35, 40, 41, 42, 43, 44, 45 and a case series37 that reported 14 cases of TTP that were refractory to PEX, steroids, and rituximab. All but one patient recovered from their acute episode of TTP.…”
Section: Bortezomibmentioning
confidence: 99%
“…Bortezomib (Velcade) [59] A myeloma multiplex kezelésében nagy sikerrel használt proteoszóma inhibitor. A terápia az ADAMTS13-antitestet termelő plazmasejtek elpusztítását célozná, ezek ugyanis rezisztensek a hagyományos immunszuppresszív terápiára.…”
Section: A Jövő Terápiás Lehetőségeiunclassified